2014
DOI: 10.1016/j.pnpbp.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and adult hippocampal neurogenesis: Promiscuous drug, wanton effects

Abstract: Adult neurogenesis is now widely accepted as an important contributor to hippocampal integrity and function but also dysfunction when adult neurogenesis is affected in neuropsychiatric diseases such as alcohol use disorders. Excessive alcohol consumption, the defining characteristic of alcohol use disorders, results in a variety of cognitive and behavioral impairments related wholly or in part to hippocampal structure and function. Recent preclinical work has shown that adult neurogenesis may be one route by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 225 publications
3
65
1
1
Order By: Relevance
“…Furthermore, a preclinical study reported reductions in accumbal volume in alcohol-naïve rats with a genetic predisposition to alcohol addiction (Gozzi et al, 2013), suggesting that accumbal volume reductions may be a pre-existing condition resulting in a vulnerability to alcohol addiction. ADO individuals also had decreased hippocampal volume, which is consistent with the literature on the hippocampal volume and alcohol use disorder (Agartz et al, 1999; Fein and Fein, 2013; Sullivan et al, 1995; Wrase et al, 2008), and corresponds to preclinical findings of hippocampal neurodegeneration due to alcohol exposure (Geil et al, 2014). There was also decreased volume in the right thalamus in both ADO and PS individuals, and decreased left thalamic volume in PS individuals.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, a preclinical study reported reductions in accumbal volume in alcohol-naïve rats with a genetic predisposition to alcohol addiction (Gozzi et al, 2013), suggesting that accumbal volume reductions may be a pre-existing condition resulting in a vulnerability to alcohol addiction. ADO individuals also had decreased hippocampal volume, which is consistent with the literature on the hippocampal volume and alcohol use disorder (Agartz et al, 1999; Fein and Fein, 2013; Sullivan et al, 1995; Wrase et al, 2008), and corresponds to preclinical findings of hippocampal neurodegeneration due to alcohol exposure (Geil et al, 2014). There was also decreased volume in the right thalamus in both ADO and PS individuals, and decreased left thalamic volume in PS individuals.…”
Section: Discussionsupporting
confidence: 89%
“…AIE has been associated with dysfunction in key learning and memory structures in adult rodents. Although AIE leads to decreased neurogenesis within the hippocampus (Geil et al, 2014; Vetreno and Crews, 2015; Sakharkar et al, 2016), AIE’s detrimental effects on spatial memory are inconclusive (Risher et al, 2013; Swartzwelder et al, 2015; Beaudet et al, 2016). Following AIE, there is also a significant loss in the number of cholinergic neurons within the medial septum/diagonal band (MS/DB), which projects to the hippocampus, and the Nucleus basalis of Meynert (NbM) that projects to the cortex (Ehlers et al, 2011; Vetreno et al, 2014; Boutros et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that alcohol is involved in the regulation of adult neurogenesis by controlling NSPC proliferation [117, 118]. Alcohol was shown to inhibit NSPC proliferation in adult rats with the paradigms of both acute and chronic binge underlying alcoholic cognitive dysfunction.…”
Section: Modulation Of Nspcs By Addictive Drugs and Underlying Mechanmentioning
confidence: 99%